2017
DOI: 10.1007/s11095-017-2166-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone Based Nanoparticles Loaded with Indomethacin for Anti-Inflammatory Therapy: From Preparation to Ex Vivo Study

Abstract: The prepared nanoparticles are submicron in nature, with good colloidal stability and penetrate the stratum corneum layer of the skin. This formulation potentiates IND skin penetration and as a promising strategy would be able to decline the side effects of IND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…Owing to its high permeability for small drug molecules [10], the aliphatic polyester, PCL represents an important candidate for fabricating carriers for drug delivery applications, including: microparticles [11], nanoparticles [12], microspheres [13], coatings [14], and scaffolds [15]. However, due to its intrinsic high hydrophobicity and crystallinity, PCL degrades rather slowly.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high permeability for small drug molecules [10], the aliphatic polyester, PCL represents an important candidate for fabricating carriers for drug delivery applications, including: microparticles [11], nanoparticles [12], microspheres [13], coatings [14], and scaffolds [15]. However, due to its intrinsic high hydrophobicity and crystallinity, PCL degrades rather slowly.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, nonsteroidal antiinflammatory drugs can cause numerous serious side effects 25. Therefore, antiinflammatory agents based on nanomaterials emerge as potent drug systems to treat RA 76…”
Section: Nanotherapeutics Of Ra Based On Nanodrugsmentioning
confidence: 99%
“…[25] Therefore, antiinflammatory agents based on nanomaterials emerge as potent drug systems to treat RA. [76] Curcumin, a major extraction derived from turmeric, has excellent antitumor, antimicrobial, and antioxidant properties. Owing to these predominant properties, Cur has been used as therapeutic agents for various diseases such as chronic inflammatory, diabetes, cutaneous diseases, and so forth.…”
Section: Antiinflammatory Therapymentioning
confidence: 99%
“…In contrast to previous investigations on PCL-based microspheres and lms, we demonstrate here for the rst time that we can design nanocarriers based on PCL with diol functionality that allow for a fast payload release of hydrophilic compounds depending on the number of degradable segments and the morphology of the nanocarriers (which is usually not the case if polycaprolactone is used as a biodegradable polymer). 63,64 As compared to other commonly used biodegradable polymers such as polylactic acid, poly glycolic acid, and poly(lactic-co-glycolic acid), polycaprolactone degrades slowly due to the latter's hydrophobicity and crystallinity. 65 However, based on the obtained results via our elegant interfacial formulation procedure, we have shown that the degradation prole can be tuned.…”
Section: Ph-dependent Release Kineticsmentioning
confidence: 99%